Pointwise convergent expansions in q-Fourier-Bessel series - Abreu, L. D. (2006)
We define q-analogues of Fourier-Bessel series, by means of complete q- orthogonal systems constructed with the third Jackson q-Bessel function. Sufficient conditions for pointwise convergence of these series are obtained, in terms of a general convergence principle valid for other Fourier series on grids defined over numerable sets. The results are illustrated with specific examples of developments in q-Fourier-Bessel series.